Episodic and non-uniform shifts of thermal habitats in a warming ocean. (March 2015) - Sen Gupta, A.; Brown, J.N.; Jourdain, N.C.; van Sebille, E.; Ganachaud, A.; Vergés, A.
Abstract: Ocean temperatures have warmed in most regions over the last century and are expected to warm at a faster rate in the future. Consistent with the view that marine species are thermally constrained, there is growing evidence that many marine species have already undergone poleward range shifts in line with warming trends. This study uses historical observations of ocean temperature and climate model projections to examine the movement of isotherms that mark the boundaries for species′ thermal habitats. In particular, we compare the rates of isotherm movement between different ocean regions and at different time scales and examine to what extent the implied movement is uniform or sporadic. Widespread long-term warming implies poleward shifts of isotherms in almost all regions. However, as the speed of isotherm movement is inversely related to local meridional SST gradients and the pattern of ocean warming is heterogeneous, speeds vary considerably between regions, season and over time. At present on decadal and longer timescales, changes due to low frequency natural SST variability can dominate over human-induced changes. As such, there are multidecadal periods in certain regions when we would expect to see range shifts that are much faster or in the opposite direction to that implied by a monotonic warming. Based on central estimates from the latest suite of climate model projections, median isotherm speeds will be about seven times faster in the 21st century compared to the 20th century under business as usual emissions. Moreover, SST warming is projected to be greater in summer than in winter in most oceanic regions, contrary to what is projected to occur over land. As such net poleward isotherm speeds, particularly in the northern hemisphere summer, are projected to be considerably faster than in winter. Finally we show that isotherms can exhibit erratic migration rates over time, even under uniform warming. Isotherm movement tends to stall at thermal fronts for extended periods of time and then rapidly shift to a new position, marked by more poleward fronts. This implies that species ranges would also be expected to undergo sudden rapid shifts rather than exhibiting a gradual monotonic poleward march.